EKSISTENSI PENDIDIKAN DAN NILAI KEISLAMAN TRADISI SAPRAHAN MELAYU SAMBAS SERTA PERAN TOKOH MASYARAKAT DALAM MELESTARIKANNYA - Kautsar, Ibmu (STIT Al-Ittihadiyah Labuhanbatu Utara, 2023)
Sambas has inherited a lot of cultural wealth, one of the richest in West Kalimantan. One of these assets is the Saprahan tradition. This article is intended to reveal the existence and cultivation of Islamic values and the role of community leaders in preserving this tradition. This study uses the method of library research (library research). The Saprahan tradition was discovered when the Sambas Kingdom became an Islamic power. The saprahan tradition symbolizes the value of religious teachings as a pillar of Islamic teachings. The Islamic values contained in it include mutual cooperation, mutual help, togetherness and equality among human beings. The role of community leaders is very important in guiding, motivating and nurturing the community in preserving this tradition.